Self-employment after socialism: Intergenerational links, entrepreneurial values, and human capital - Michael Fritsch; Alina Rusakova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Drawing on representative household data from the German Socio-Economic Panel, we examine the role of an early precursor of entrepreneurial development - parental role models - for the individual decision to become self-employed in the post-unified Germany. The findings suggest that the socialist regime significantly damaged this mechanism of an intergenerational transmission of entrepreneurial attitudes among East Germans with a tertiary degree that have experienced a particularly strong ideological indoctrination. However, we find a significant and positive relationship between the presence of a parental role model and the decision to become self-employed for less-educated people. For West Germans the positive relationship holds irrespective of the level of education.
Keywords: L26; Z1; D03; 330; Entrepreneurship; parental role models; human capital; Unternehmer; Selbstständige; Entscheidung; Bildungsniveau; Systemtransformation; Neue Bundesländer; Generationenbeziehungen; Alte Bundesländer; Deutschland